2018
DOI: 10.1097/bsd.0000000000000663
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Freehand Sagittal Trajectories for Inserting Pedicle Screws Between C7 and T5

Abstract: Study Design:Anatomic study using computed tomographic scans.Objective:The purpose of this paper was to determine the trajectory of pedicle screw insertions, in regard to posterior bony landmarks encountered during standard posterior exposure of the spine between the seventh cervical (C7) and the fifth thoracic (T5) vertebrae, when lateral fluoroscopic and radiographic guidance may be obstructed by the scapula and shoulders.Summary of Background Data:Only a few studies have evaluated the intraoperative sagitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…However, detailed measurements of the individual vertebrae or the identification of vertebral zones were not analyzed. Furthermore, Oshina et al [15] reported that the ideal sagittal trajectories for pedicle screw insertions were nearly orthogonal to the lamina surface or to the line connecting spinous processes. However, they were different for each vertebra, although the lamina surface method was most reliable for the C7-T1 vertebrae [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, detailed measurements of the individual vertebrae or the identification of vertebral zones were not analyzed. Furthermore, Oshina et al [15] reported that the ideal sagittal trajectories for pedicle screw insertions were nearly orthogonal to the lamina surface or to the line connecting spinous processes. However, they were different for each vertebra, although the lamina surface method was most reliable for the C7-T1 vertebrae [15].…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have focused on screw inclination in the mediolateral direction [1,[8][9][10], few have addressed sagittal plane assessment [11][12][13][14]. To determine the correct sagittal trajectory of the thoracic pedicle screw, bony landmarks, such as the lamina surface, the spinous process, and the facet joint tilt can be used as anatomic references [15]. Based on observations in different spinal disorders, including deformities, it was noted that following a sagittal cranial-caudal trajectory perpendicular to the interlaminar line (ILL) joining the two adjacent vertebrae would work well at most vertebral levels.…”
Section: Introductionmentioning
confidence: 99%
“…In the upper thoracic spine, obtaining a proper lateral view with fluoroscopy is difficult due to the superimposition of the shoulder. 5 Furthermore, in patients with vertebral body fracture, there is significant kyphosis in the proximal vertebral levels that will alter the sagittal angulation of screws. For accurate pedicle screw placement, many image-guided technologies have been developed; however, its cost-effectiveness is debatable.…”
Section: Introductionmentioning
confidence: 99%
“…6 There are a few studies that have addressed assessing the sagittal-plane orientation of the pedicle screw. 5,[7][8][9][10][11][12] The previously published methods of determining the sagittal angulation of a pedicle screw in vivo can only provide a vague visual cue to the surgeon, which will result in human errors. 5,[7][8][9][10][11][12] It is known that even experienced spine surgeons cannot aim for a predefined angulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation